Large‐Scale and Wide‐Gamut Coloration at the Diffraction Limit in Flexible, Self‐Assembled Hierarchical Nanomaterials. Issue 11 (3rd February 2022) - Li, Ning; Xiang, Fei; Elizarov, Maxim S.; Makarenko, Maxim; Lopez, Arturo B.; Getman, Fedor; Bonifazi, Marcella; Mazzone, Valerio; Fratalocchi, Andrea
Abstract: Unveiling physical phenomena that generate controllable structural coloration is at the center of significant research efforts due to the platform potential for the next generation of printing, sensing, displays, wearable optoelectronics components, and smart fabrics. Colors based on e‐beam facilities possess high resolutions above 100k dots per inch (DPI), but limit manufacturing scales up to 4.37 cm 2, while requiring rigid substrates that are not flexible. State‐of‐art scalable techniques, on the contrary, provide either narrow gamuts or small resolutions. A common issue of current methods is also a heterogeneous resolution, which typically changes with the color printed. Here, a structural coloration platform with broad gamuts exceeding the red, green, and blue (RGB) spectrum in inexpensive, thermally resistant, flexible, and metallic‐free structures at constant 101 600 DPI (at the diffraction limit), obtained via mass‐production manufacturing is demonstrated. This platform exploits a previously unexplored physical mechanism, which leverages the interplay between strong scattering modes and optical resonances excited in fully 3D dielectric nanostructures with suitably engineered longitudinal profiles. The colors obtained with this technology are scalable to any area, demonstrated up to the single wafer (4 in.). These results open real‐world applications of inexpensive, high‐resolution, large‐scale structural colors with broad chromatic spectra. Abstract : A dielectric structural coloration platform that simultaneously addresses all areas required for real‐world commercial applications is implemented: wide colors gamut, also exceeding the red, green, and blue (RGB) spectrum, low manufacturing costs, large‐scale printing demonstrated on entire wafers and 4 in. flexible substrates, and high printing resolutions at a constant 101 600 dots per inch.